2019
DOI: 10.3389/fphar.2019.00647
|View full text |Cite
|
Sign up to set email alerts
|

Myricetin Attenuated Diabetes-Associated Kidney Injuries and Dysfunction via Regulating Nuclear Factor (Erythroid Derived 2)-Like 2 and Nuclear Factor-κB Signaling

Abstract: Background/Aims: Previous studies have suggested that myricetin (Myr) could promote the expression and nuclear translocation of nuclear factor (erythroid-derived 2)-like (Nrf2). This study aimed to investigate whether Myr could attenuate diabetes-associated kidney injuries and dysfunction in wild-type (WT) and Nrf2 knockdown (Nrf2-KD) mice. Methods: Lentivirus-mediated Nrf2-KD and WT mice were used to establish type 1 diabetes mellitus (DM) by streptozotocin (STZ) injection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…Of note, our results further revealed that myricetin led to inhibiting LPS-induced TREM-1-mediated inflammatory response via downregulation of NF-κB activation and reducing the phosphorylation of STAT3 and JNK expression as shown by our western blotting (Figure 8). These findings were consistent with previous studies exhibiting that myricetin attenuated inflammatory response in LPS-induced macrophages in vitro and in streptozotocin-induced diabetic nephropathy by inhibiting NF-κB signaling pathways (28,37).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Of note, our results further revealed that myricetin led to inhibiting LPS-induced TREM-1-mediated inflammatory response via downregulation of NF-κB activation and reducing the phosphorylation of STAT3 and JNK expression as shown by our western blotting (Figure 8). These findings were consistent with previous studies exhibiting that myricetin attenuated inflammatory response in LPS-induced macrophages in vitro and in streptozotocin-induced diabetic nephropathy by inhibiting NF-κB signaling pathways (28,37).…”
Section: Discussionsupporting
confidence: 93%
“…Group B or C: mice were fed CDAHFD with orally administration myricetin at 100 mg/kg per day or vehicle ( Figure 1B). The doses of myricetin were chosen based on previous studies in mice (28,32,37). At the end of treatment period, mice were euthanized using ketamine/xylazine, blood samples were collected via cardiac puncture to detect biochemical biomarkers.…”
Section: Animals and Experimental Protocolsmentioning
confidence: 99%
“…Treatment with Nrf2 activators, tert-butylhydroquinone (TBHQ) [293], bardoxolone methyl analog [294], or sulforaphane [295], reduced expression of proinflammatory cytokines and macrophage infiltration in preclinical models of DN. Furthermore, other compounds with the ability to promote Nrf2 translocation, such as omentin-1, and natural flavonoids (myricetin, hesperetin, and curcumin), improve renal function and reduces proinflammatory cytokine production in DN [296][297][298][299]. Particularly, dietary supplementation with curcumin increased the antioxidant capacity, reduced microalbuminuria and plasma MDA levels of patients with DN [300,301].…”
Section: Nrf2mentioning
confidence: 99%
“…Myricetin exhibited antioxidant properties and free radical-scavenging effects [19]. These activities seem to support a wide range of beneficial outcomes including, anti-platelet aggregation, antihypertensive, immunomodulatory, anti-inflammatory, anti-allergic, analgesic, anticancer actions and so on [6,[20][21][22][23][24][25]. The main goal of the present review is to provide new insights on myricetin preclinical pharmacological activities, and its role in selected clinical trials.…”
Section: Introductionmentioning
confidence: 99%